Exploring the Potential of Task-Based Language Teaching (TBLT) for Teaching Second Languages with Complex Morphological Systems - Udes, Richard (Verbum, 2025)
The acquisition of morphosyntactic structures represents one of the most significant challenges for second language (L2) learners, particularly in languages with complex morphological systems, such as Lithuanian. The intricacy of these systems, coupled with the abundance of morphemes, further complicates the learning process for L2 students. Although task-based language teaching (TBLT) has been recognized as an effective methodology for L2 instruction, limited research has explored its applicability to languages characterized by high morphological complexity. A prevailing assumption suggests that TBLT may be unsuitable for such languages, particularly at the beginner stages (Kogan & Bondarenko, 2022, pp. 78–79). Nonetheless, this perspective calls for further scrutiny. This paper aims to contribute to the ongoing discourse by examining how to design effective instructional tasks across proficiency levels for teaching morphologically complex L2s while adhering to all the TBLT principles.